MAKING OF TREATMENT OF AUCTION DEED FOR NOTARY BY METHOD CYBER NOTARY - Mursalati Urfa; Abdul Halim Barkatullah; Saprudin Saprudin (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2023)
This research is legal research normative using a statutory approach (statute approach) and a conceptual approach (conceptual approach) to analyze the problem, pThis research aims to examine and analyze the auction treatise deed made by a notary by cyber notary, where the conceptcyber notary turns out to have a norm conflict with Article 16 paragraph (9) regarding the word element before which is a formal requirement for the validity of an authentic deed as stated in Article 16 paragraph (9) regarding the position of Notary. Apart from that, there is also legal obscurity in Article 15 paragraph (2) letter g of the UUJN, for this reason, a revision of the UUJN is needed, especially in Article 15 paragraph (2) letter g by adding a clause that a notary who can make auction minutes is a notary who has been appointed first by the Minister of Finance of the Republic of Indonesia.